Determinants of self-management behaviors among pulmonary tuberculosis patients: a path analysis - Jin Li; Jie Pu; Jiaqing Liu; Qingya Wang; Rui Zhang; Ting Zhang; Jiani Zhou; Wei Xing; Shengxiang Liang; Daiyu Hu; Ying Li (BMC, 2021)
Abstract Background Tuberculosis (TB) is one of the top 10 causes of death in the world. Since Directly Observed Therapy (DOT) as a core strategy for the global TB control are not applicable to all types of TB patients, and self-management of TB patients (SMTP) as a patient-centered supervision type is a supplement to DOT and can improve TB case management. However, the factors related to SMTP are complex and need more study. This study aimed at identifying the determinants of SMTP and examining the direct/indirect effects of these determinants. Methods The purposive sampling technique was used to select study sites and participants were recruited from the study sites by the consecutive sampling method. The PRECEDE model was used as the framework to analyze the determinants of SMTP. The responses of TB patients were acquired via a questionnaire survey for data collection. A Pearson correlation analysis was used to define the relationship between the predisposing, enabling, reinforcing factors with SMTP behaviors. A regression-based path analysis was used to determine the action paths of the predisposing, enabling, and reinforcing factors on SMTP behaviors. Results The predisposing (TB knowledge), enabling [health education and healthcare workers (HCWs) support], reinforcing factors (family support) had significant positive correlations with SMTP behaviors (P < 0.05). The predisposing, enabling, reinforcing factors were positively correlated with each other (r = 0.123‒0.918, P < 0.05), except for family support and HCWs support. The predisposing factors (TB knowledge, β = 0.330) and the enabling factors (HCWs support, β = 0.437) had direct effects on SMTP behaviors. The enabling factors (health education and HCWs support) and the reinforcing factors (family support) had indirect effects on SMTP behaviors. Conclusions This study revealed the effects and action path of TB knowledge, health education, HCWs support, and family support on SMTP behaviors via a path analysis. Assessing patient's needs for SMTP along with promoting effective TB health education and providing firm support from HCWs and family members are potential strategies to promote SMTP behaviors. Graphic abstract